2015
DOI: 10.1016/j.actamat.2015.07.044
|View full text |Cite
|
Sign up to set email alerts
|

Glide dislocation nucleation from dislocation nodes at semi-coherent {1 1 1} Cu–Ni interfaces

Abstract: a b s t r a c tUsing atomistic simulations and dislocation theory on a model system of semi-coherent {1 1 1} interfaces, it is shown that misfit dislocation nodes adopt multiple atomic arrangements corresponding to the creation and redistribution of excess volume at the nodes. Four distinctive node structures were identified: volume-smeared nodes with (i) spiral or (ii) straight dislocation patterns, and volume-condensed nodes with (iii) triangular or (iv) hexagonal dislocation patterns. Volume-smeared nodes c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(31 citation statements)
references
References 59 publications
(103 reference statements)
1
30
0
Order By: Relevance
“…Much recent MD simulation-based research has addressed the strengthening eff ects of interfaces and the underlying micromechanisms (Shao and Medyanik (2010); Shao et al (2015); Mitchell (2002); Rao and Hazzledine (2000); Wang et al (2008b,a); Ghosh and Arroyo (2013); Peng and Wei (2016); Zhu et al (2015); Salehinia et al (2014); Li et al (2012b); Zbib et al (2011);). However, studies using MD simulations to understand the atomic-scale details of interactions between shockwaves and interfaces have been infrequent.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Much recent MD simulation-based research has addressed the strengthening eff ects of interfaces and the underlying micromechanisms (Shao and Medyanik (2010); Shao et al (2015); Mitchell (2002); Rao and Hazzledine (2000); Wang et al (2008b,a); Ghosh and Arroyo (2013); Peng and Wei (2016); Zhu et al (2015); Salehinia et al (2014); Li et al (2012b); Zbib et al (2011);). However, studies using MD simulations to understand the atomic-scale details of interactions between shockwaves and interfaces have been infrequent.…”
Section: Introductionmentioning
confidence: 99%
“…As a special class of metallic multilayer materials, the mechanical behaviors of Cu-Ni multilayers have attracted significant recent interest (Misra et al (1998); ; Liu et al (2011a); Rao and Hazzledine (2000); Mitchell (2002); Yan et al (2013); Liu et al (2012); Yahalom et al (1989)). Shao et al (2013Shao et al ( , 2014Shao et al ( , 2015 recently reported observations from MD simulations of misfit dislocation structures in Cu(111)/Ni(111) semi-coherent interfaces. They found that the interfaces contained several structures, including normal FCC stacking structures, intrinsic stacking-fault structures, misfit dislocations, and misfit dislocation intersections (nodes).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The triangular nodes can transform into an expanded hexagonal structure (Figure 4d) when it is relaxed at a finite temperature of above 10 K. This structure has been observed in the experiment. This structure, referred to as the volume-condensed node with hexagonal dislocation pattern, is formed from the triangular nodes after a series of complex dislocation reactions (detailed information in [46]). The dislocation structure of the node also involves two adjacent (111) planes (Ni1-Cu1 and Cu1-Cu2).…”
Section: Structures and Properties At Nodesmentioning
confidence: 99%
“…16 Recently, dislocation-interface interaction mechanisms have been proposed for the dislocation nucleation and transmission for low-energy interfaces, such as the semi-coherent Cu{111}/{111}Ni interfaces 14,17 and Kurdjumov-Sachs (KS) and Nishiyama-Wassermann (NW) Cu{111}/{110}Nb interfaces. 5,6,13,18,19 These interfaces are composed of closely packed planes of two adjacent metals, which allow the cores of misfit dislocations to preferably dissociate within the interface. Such core spreading significantly reduces stress/strain concentrations at the interface and thus traps the dislocations there, strengthening the material by creating a high activation barrier for dislocation nucleation.…”
mentioning
confidence: 99%